Development of higher order thinking using a module based on cognitive apprenticeship model for year five students on the topic of measurement and geometry - Noor Ibrahim, Noorashikim (2018)
Higher Order Thinking Skills (HOTS) are recognized as an important goal in Malaysian education. However, there is little empirical evidence to help educators decide how to teach in ways that infuse HOTS in the content knowledge. The aim of this study is twofold; (i) to develop and evaluate a HOTS-based module in the topic of measurement and geometry for year five pupils; and (ii) to investigate the effectiveness of the HOTS-based module among the pupils. This study adopted ADDIE model in three phases. In Phase 1, the study is focused on the analysis of the target group’s needs which involved mathematics teachers. Phase 2 include the process in designing, developing the assessments and learning activities, and validation of HOTS-based module. In Phase 3, the aim is to evaluate the effectiveness of the module using pupils’ performance tests, problem solving skills, conceptual knowledge, and procedural knowledge. The study had adopted a quasi-experimental design involving two groups of subjects. Two hundred and ninety seven pupils from four schools involved in this intervention. The control group was exposed to the conventional learning strategy, while the experimental group used the HOTS-based Modules framed by CAM. Data was collected using performance test. Analyses on the types of errors committed by the pupils were conducted on the experimental groups. These measurements were presented in comparison between urban and rural schools in Kota Bharu, Kelantan. In Phase 1, results showed that some teachers have positive perceptions towards HOTS, whereas some of them disagree with the implementation of HOTS due to insufficient of time, inappropriate and not accordance with the student’s ability. Due to this, HOTSbased module was designed to support teachers and pupils in the face-to-face classroom sessions. In Phase 2, the validation of instruments and HOTS-based module was done by two experts from Teacher Education Institute and one from District Education Department. In Phase 3, the result showed that the use of HOTS-based module has a significant effect on pupil’s performance in two tests (post-test and post-delayed test), as well as their problem solving skills, conceptual knowledge, and procedural knowledge. Whereas for the error analysis, percentage of different types of errors committed by pupils in rural schools is more than pupils in urban schools. Pupils in the treatment group committed less errors compared to their counterpart. Specifically, the result indicated that pupils from urban school significantly better in the mean scores for performances, problem solving skills, conceptual knowledge and procedural knowledge in learning Measurement and Geometry as compared to the pupils in the rural schools. Furthermore, these results indicated that the teaching and learning process based on CAM has significantly enhanced pupils’ performance in this topic. The pupil’s interest in HOTS-based module was at high level. Almost all pupils from both urban and rural schools decided that the HOTS-based module increased their interest in mathematics, specifically in the topic of measurement and geometry.